Adoption of Different Housing Models to Access Housing by Households in Nairobi County - Kamande, Francis; Oboka, Wycliffe; Gweyi , Moses; Ngala, Michael (European Journal of Business and Strategic Management, 2023)
Purpose: This study aimed to evaluate adoption of different housing models to access housing by households in Nairobi County. Methodology: Employing a descriptive research design, the study investigates the impact of housing regulations on housing access through mortgage and cooperative models. The research sample comprises 385 households, CEOs of housing financing organizations, and government officers. Findings: The study reveals that adoption of housing model is shaped by diverse factors. The residency duration reflects both long-term and newer residents, highlighting the dynamic interplay of urban growth and migration. Notably, 35.0% of respondents have lived in their current houses for "4 - 6 years," emphasizing housing stability. The prevalent adoption of the Incremental (34.4%) and Cooperative Models (33.4%), alongside 41.4% awareness of the Mortgage Model, signifies residents' adaptability in navigating financial avenues for homeownership. Challenges like high construction costs persist, with 80% of Nairobi's population residing in informal settlements and slums. Strengthening regulatory frameworks is crucial, and policymakers should address financial barriers. This study provides insights for creating an inclusive and sustainable housing environment, essential for the 59.2% of renters expressing aspirations to transition into homeownership in Nairobi County. In conclusion, the housing landscape in Nairobi County, particularly Ruai Sub-County, reflects a mix of long-term and newer residents, emphasizing housing stability. The prevalent adoption of Incremental and Cooperative Models, along with awareness of the Mortgage Model, indicates residents' adaptability in pursuing homeownership. Unique Contribution to Theory, Practice and Policy: Utilizing the Public Interest Economic Regulation Theory (PIERT), the Q Theory of Housing Investment, and the Theory of Distributive Justice, the research explores the interplay between government regulations, market forces, and social equity in the context of affordable housing. To address challenges, policymakers should strengthen regulatory frameworks, enhance financial policies, and promote diverse housing models. Public awareness campaigns are vital. Recommendations include tailored financial products and inclusive strategies to meet the varied needs of the population. These measures aim to create an enabling environment for accessible and sustainable housing in Nairobi County, benefiting both existing and aspiring homeowners.